A Comparative Study of Some Biomechanical Variables According to Physical Biorhythm Curve Among Young High Jumpers - Mudhafar Oraibi Baieji (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aimed to identify some biomechanical variables in high jump performance of young athletes according to positive and negative biorhythm curve. It also aimed to identify differences in some biomechanical variables during positive and negative biorhythm cycles. The researcher hypothesized existence of statistically significant differences in some biomechanical variables during high jump performance of young athletes, favoring positive biorhythm cycle. The researcher used descriptive method, as it was suitable for study outcome. Four high jumpers from specialized schools participating in Southern Region Championship were selected to perform youth high jump. These athletes had achieved top rankings after homogenization of some variables. Athletes were photographed according to their positive and negative biorhythm cycles, calculated for each athlete based on their birth date and date of test. The researcher used appropriate statistical methods for outcome of study, including mean, standard deviation, t -test for paired samples, and simple correlation coefficient, to extract differences among values of biomechanical variables according to biomechanical rhythm curve. The most important conclusions of research revealed statistically significant differences in some biomechanical variables between positive and negative phases of physical cycle, favoring positive phase. No significant differences were found in angle of support and time of stand-up between positive and negative phases of physical cycle. Statistically significant differences were found in following kinematic variables stand-up knee angle, stand-up angle, and vertical speed, favoring positive phase of biomechanical rhythm cycle. The most important recommendations adoption of a systematic scientific record for recording data for each player, along with periodic monitoring of phases of biomechanical rhythm and identifying rise and fall of cycle. This will enable coaches to diagnose fluctuations in physical abilities according to cycle variables. It is necessary for trainers to pay attention to physical biorhythm cycle when preparing and implementing training programs by taking into account positive and negative phases, which contributes to regulating training loads to improve level of performance and achievement.